Ethical Theory and Stakeholder-Related Decisions: The Role of Stakeholder Culture - Jones, Thomas M.; Felps, Will; Bigley, Gregory A. (Academy of Management Review, 2007)
We use convergent elements of major ethical theories to create a typology of corporate stakeholder cultures–the aspects of organizational culture consisting of the beliefs, values, and practices that have evolved for solving problems and otherwise managing stakeholder relationships. We describe five stakeholder cultures–agency, corporate egoist, instrumentalist, moralist, and altruist–and explain how these cultures lie on a continuum, ranging from individually self-interested (agency culture) to fully other-regarding (altruist culture). We demonstrate the utility of our framework by showing how it can refine stakeholder salience theory.